2020
DOI: 10.3390/toxics8030065
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Toxicity and Degradation Mechanisms of Imidacloprid Via Physicochemical and Microbial Approaches

Abstract: Imidacloprid is a neonicotinoid insecticide that has been widely used to control insect pests in agricultural fields for decades. It shows insecticidal activity mainly by blocking the normal conduction of the central nervous system in insects. However, in recent years, imidacloprid has been reported to be an emerging contaminant in all parts of the world, and has different toxic effects on a variety of non-target organisms, including human beings, due to its large-scale use. Hence, the removal of imidacloprid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 156 publications
(216 reference statements)
0
30
0
Order By: Relevance
“…Out of the five start products, which have no apparent connection to DON exposure, products B and E, were able to biotransform the mycotoxin completely, starting from the first enrichment. During the subsequent enrichments of product B, a shift in bacterial community was observed towards mainly the genera Sphingopyxis , Pseudoxanthomonas , Ochrobactrum and Pseudarthrobacter , which are known for their biodegradation capabilities of complex molecules, such as (polycylic) aromatic hydrocarbons [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ], neonicotinoid insecticides [ 69 ], cyanobacterial toxins [ 66 , 70 , 71 ], phthalate esters [ 72 ], polyhydroxyalkanoates [ 73 ], nitrophenols [ 74 ], 2,4,6-trinitrotoluene [ 75 ], etc. The classes to which these genera belong, the α-, γ-proteobacteria and Actinobacteria, are also linked to the bioremediation and biodegradation of other mycotoxins such as aflatoxins, fumonisins, zearalenone and ochratoxins [ 76 , 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Out of the five start products, which have no apparent connection to DON exposure, products B and E, were able to biotransform the mycotoxin completely, starting from the first enrichment. During the subsequent enrichments of product B, a shift in bacterial community was observed towards mainly the genera Sphingopyxis , Pseudoxanthomonas , Ochrobactrum and Pseudarthrobacter , which are known for their biodegradation capabilities of complex molecules, such as (polycylic) aromatic hydrocarbons [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ], neonicotinoid insecticides [ 69 ], cyanobacterial toxins [ 66 , 70 , 71 ], phthalate esters [ 72 ], polyhydroxyalkanoates [ 73 ], nitrophenols [ 74 ], 2,4,6-trinitrotoluene [ 75 ], etc. The classes to which these genera belong, the α-, γ-proteobacteria and Actinobacteria, are also linked to the bioremediation and biodegradation of other mycotoxins such as aflatoxins, fumonisins, zearalenone and ochratoxins [ 76 , 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial degradation is regarded as a cost-effective and promising method with a huge potential for the removal of pesticides, compared to physicochemical approaches [ 9 , 13 , 19 ]. Soil bacteria and fungi have been documented as being able to mineralize various organic pollutants as a sole carbon source [ 56 , 57 , 58 , 59 , 60 ].…”
Section: Microbial Degradation Of Ddvpmentioning
confidence: 99%
“…Several microbes, including Cunninghamell aelegans , Fusarium solani , Talaromyces atroroseus , Aspergillus oryzae , Ochrobactrum intermedium , Pseudomonas aeruginosa , and Penicillium sp., have been isolated and play vital roles in DDVP degradation. It has been reported that the organic pollutants can be used by edaphon including soil bacteria and soil fungi as a sole carbon source [ 9 , 10 , 11 , 12 , 13 ]. These studies showed that microbial degradation seems to be a more environmentally friendly and convenient treatment method to reduce hazardous effects of toxic pollutants or contaminants [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of degradation of neonicotinoids varies according to microbial community composition and function [ 77 ]. Using controlled experimental conditions in the laboratory, Anhalt et al [ 78 ] reported that Leifsonia strain PC-21 degraded up to 58% from 25 mg/L imidacloprid within three weeks in trypsin solution containing 1 g/L succinate and D-glucose at 27 °C while the control (i.e., without Leifsonia strain PC-21) had no degradation of imidacloprid.…”
Section: Neonicotinoidsmentioning
confidence: 99%